Fanconi Anemia Repair Pathway Dysfunction, a Potential Therapeutic Target in Lung Cancer - Duan, Wenrui; Gao, Li; Aguila, Brittany; Kalvala, Arjun; Otterson, Gregory A.; Villalona-Calero, Miguel A. (Frontiers in Oncology, 2014)
The Fanconi Anemia (FA) pathway is a major mechanism of homologous recombination DNA repair. The functional readout of the pathway is activation through mono-ubiquitination of FANCD2 leading to nuclear foci of repair. We have recently developed an FA triple staining immunofluorescence based method (FATSI) to evaluate FANCD2 foci formation in formalin fixed paraffin embedded (FFPE) tumor samples. DNA repair deficiencies have been considered of interest in lung cancer prevention, given the persistence of damage produced by cigarette smoke in this setting, as well as in treatment, given potential increased efficacy of DNA damaging drugs. We screened 139 non-small cell lung cancer (NSCL) FFPE tumors for FANCD2 foci formation by FATSI analysis. Among 104 evaluable tumors, 23 (22%) were FANCD2 foci negative, thus repair deficient. To evaluate and compare novel targeted agents in the background of FA deficiency we utilized RNAi technology to render several lung cancer cell lines FANCD2 deficient. Successful FANCD2 knockdown was confirmed by reduction in the FANCD2 protein. Subsequently, we treated the FA defective H1299D2-down and A549D2-down non-small cell lung cancer cells and their FA competent counterparts (empty vector controls) with the PARP inhibitors veliparib (ABT-888) (5µM) and BMN673 (0.5µM), as well as the CHK1 inhibitor Arry-575 at a dose of 0.5M. We also treated the FA defective small cell lung cancer cell lines H719D2-down and H792D2-down and their controls with the BCL2/XL inhibitor ABT263 at dose of 2 M. The treated cells were harvested at 24, 48 and 72 hours post treatment. MTT cell viability analysis showed that each agent was more cytotoxic to the FANCD2 knock-down cells. In all tests, the FA defective lung cancer cells had less viable cells as comparing to controls 72 hours post treatment. Both MTT and clonogenic analyses comparing the two PARP inhibitors, showed that BMN673 was more potent compared to veliparib. Given that FA pathw